Cicatricial Ectropion Secondary to Psoriatic Arthritis - Carolina P. B. Gracitelli; Tammy Hentona Osaki; Natalia Yumi Valdrighi; Giovanni André Pires Viana; Midori Hentona Osaki (Case Reports in Ophthalmological Medicine)
Ectropion is characterized by the eversion of the eyelid margin and the consequent exposure of the conjunctiva and cornea. The shortening of the anterior lamella of the lid causes cicatricial ectropion. We described a case of skin pathology causing cicatricial ectropion. The case is about a 68-year-old woman with a 2-year history of psoriatic arthritis. She complained of eyelid tearing and redness for two years. Due to the psoriasis, she presented a very dry skin, also in the periocular region, resulting in cicatricial ectropion. A skin graft was indicated to correct the eyelid malposition. Careful investigation should be performed in patients who have a skin disease that can lead to cicatricial ectropion.